Equity of access: Requirements of Indigenous families and communities to ensure equitable access to government-approved childcare settings in Australia. - Jackiewicz, S.; Saggers, Sherry; Frances, Kate (Early Childhood Australia, 2011)
This article is concerned with the interplay between Indigenous children and their families’ equitable access to government-approved childcare services and their respective participation in such services. Specifically, it focuses on key factors that affect access and that serve as barriers to participation. The paper draws upon a national consultation funded by the Australian Government and conducted throughout 2005–2006 to respond to these concerns, and is situated within a substantial body of work which already provides a context for Indigenous children’s access to, and participation in, early childhood services. In recognition of the diverse circumstances and requirements of Indigenous families, the research methods included focus groups, community consultations, and interviews with other stakeholders in the childcare sector nationally. An analysis of national and international literature on the research theme was made. The research findings correspond with other studies in this area, highlighting that accessibility (availability of places and transport), affordability, acceptability, and appropriateness are indicators which measure how well—or not—a service is meeting the needs of Indigenous children, their families and communities in relation to child care. To ensure that all children have equitable access to the service best suited to their needs, the Commonwealth of Australia, together with all states and territories, must understand and incorporate these requirements in childcare service provision for all Indigenous children.